POSTPARTUM FAMILY PLANNING IN DKI JAKARTA: RUN CHART ANALYSIS - Siti Fatimah; Dadan Erwandi; Sabarinah Prasetyo (Jurnal Biometrika dan Kependudukan (Journal of Biometrics and Population), 2022)
Maternal Mortality Rate (MMR) is one of the national health indicators to achieve the success of maternal health efforts where the number of MMR in Indonesia reached 305 per 100,000 live births. Family planning services including Post Partum Family Planning/Keluarga Berencana Pascapersalinan (KBPP) can effectively reduce maternal mortality by reducing births and reducing high risk. The high number of KBPP users in DKI Jakarta can be caused by many things such as local government support, level of service by health workers, and others. Therefore, this study aims to analyze and find out the special causes that cause the number of KBPP participants in DKI Jakarta and as a lesson learned for other local governments. This research is a descriptive study to see the variety of data on the number of KBPP participants in DKI Jakarta. Univariate analysis was used to describe the number of KBPP participants and bivariate analysis to explain the characteristics of the variables studied based on time, namely in the form of a run chart. Based on four tests that have been carried out on the data on the number of KBPP participants in DKI Jakarta, it can be said that there is one test that meets the requirements as a variation of system data so that there is a special cause that causes the number of KBPP participants in 2019-2020. The existence of policy support from the DKI Jakarta Provincial Government, and various stakeholders has resulted in high coverage of the use of postpartum family planning.